Expression of CD3 Levels of Tumor Infiltrating Lymphocytes (TILs) in Various Grades of Oral Squamous Cell Carcinoma of Tertiary Care Hospitals of Peshawar - Natasha Kamran, Sadaf Alam, Sabeen Nasir, Karishma Ali, Shabana Bakhtiar, Arooj Khurshid, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The diagnosis of oral squamous cell carcinoma occurs late in the disease. Poor prognosis of the patient is directly correlated with the occurrence of metastatic lesions. Lymphocytes that have invaded tumors significantly influence how well cancers respond to treatment. Objectives: The objective of the study was to compare the immunohistochemical expression of CD3 TILs receptor in various grades of oral squamous cell carcinoma. Materials and Methods: This study was a retrospective comparative cross sectional (Analytical) study. It was conducted at Department of Pathology, Peshawar Medical College from August 2020 to August 2021. Sample size was calculated through G Power and 104 patients were included in the study. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) version 20.0. Chi Square test was performed for categorical variables. Results: It was observed in our study that the mean age of OSCC was 59.16 ± 13.549 SD. Half of the cases were > 60 years (n= 52, 50%) and half of the cases were < 60 years (n= 52, 50%). The male to female ratio was approximately 2:1. The most common site involved by OSCC was buccal mucosa (n=39, 37.5 %) followed by tongue (n = 31, 29.8 %). Most OSCC were well differentiated (n=54, 51.9%), followed by moderately differentiated cases (n=29, 27.9%) and poorly differentiated (n=21 cases, 20.2 %). The p value hence showed a significant difference for intratumoral and intrastromal CD3 TILs expression and grades of OSCC cases (P- value <0.0001). Conclusion: Well-differentiated oral squamous cell carcinoma has the highest CD3 TILs level, followed by moderately and poorly differentiated OSCC. Keywords: Tumor Infiltrating Lymphocytes, Tumor Microenvironment, CD3, Immunohistochemistry